2020
DOI: 10.1007/s10712-020-09586-5
|View full text |Cite
|
Sign up to set email alerts
|

Space-Based Earth Observations for Disaster Risk Management

Abstract: As space-based Earth observations are delivering a growing amount and variety of data, the potential of this information to better support disaster risk management is coming into increased scrutiny. Disaster risk management actions are commonly divided into the different steps of the disaster management cycle, which include: prevention, to minimize future losses; preparedness and crisis management, often focused on saving lives; and post-crisis management aiming at re-establishing services supporting human act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 141 publications
(149 reference statements)
0
32
0
2
Order By: Relevance
“…It is important to note that the above represents an optimum situation and delays due to image acquisition may vary ending up in reduced response from EO (up to three days). Nevertheless, this is not related to our current capacity to access and process the data practically in real time (Le Cozannet et al 2020 ).…”
Section: Resultsmentioning
confidence: 98%
“…It is important to note that the above represents an optimum situation and delays due to image acquisition may vary ending up in reduced response from EO (up to three days). Nevertheless, this is not related to our current capacity to access and process the data practically in real time (Le Cozannet et al 2020 ).…”
Section: Resultsmentioning
confidence: 98%
“…Improvements in the resolution of earth observation imagery also allow relevant information to be derived for assessing the vulnerability of exposed assets. Satellite imagery has sufficient resolution to provide basic structural characteristics (building shape, materials) that can be complemented by other survey methods including sample visits to provide assessments of structural vulnerability to different types of hazards (Le Cozannet et al 2020). For example, one assessment of structural vulnerability to earthquakes in Padang (Indonesia) found that a model using satellite imagery verified by sample site visits was able to provide a catalogue of municipal building vulnerability with fairly high accuracy (error rate of 10%) (Geiß, Klotz, and Taubenböck 2014).…”
Section: Vulnerabilitymentioning
confidence: 99%
“…A comprehensive assessment of vulnerability to hazards should also account for other factors beyond the structural vulnerability of buildings or infrastructure. Earth observations of nighttime light intensity can provide useful information on local population levels (Le Cozannet et al 2020). Big data analytical techniques such as machine learning and deep learning have been successfully used to analyze earth observation and street-level imagery to identify indicators of poverty and well-being in regions in Africa and India not wellcovered by census data (Lee et al 2020;Yeh et al 2020).…”
Section: Vulnerabilitymentioning
confidence: 99%
“…Although of importance, coastal hazards related to ice (e.g., for navigation safety on sea-ice or ice-infested coastal waters, permafrost thaw, etc.) and plastic pollution (Viatte et al 2020) are left out of this review, and so do the aspects related to the assessment of exposure and vulnerability, such as urbanisation and land management practices (Le Cozannet et al 2020). Current gaps and perspectives or recommendations on using EO for a reliable evaluation and prediction of coastal hazards are discussed in the final section.…”
Section: Introductionmentioning
confidence: 99%